2023
DOI: 10.1073/pnas.2219855120
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric communication between ligand binding domains modulates substrate inhibition in adenylate kinase

Abstract: Enzymes play a vital role in life processes; they control chemical reactions and allow functional cycles to be synchronized. Many enzymes harness large-scale motions of their domains to achieve tremendous catalytic prowess and high selectivity for specific substrates. One outstanding example is provided by the three-domain enzyme adenylate kinase (AK), which catalyzes phosphotransfer between ATP to AMP. Here we study the phenomenon of substrate inhibition by AMP and its correlation with domain motions. Using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 48 publications
3
9
0
Order By: Relevance
“…Significantly, a similar hybrid mode of ligand binding has been proposed by previous simulations by Matsunaga et al, and these results are supported by experiments by Ådén et al, who have extensively studied the surface of ligand binding using ATP as a probe molecule . In addition, our results have implications for understanding the allosteric communication between AMP binding and ATP lid closure rates, which is recently proposed by Scheerer et al In particular, they observed increased rates of ATP lid closure in the presence of AMP, while AMP did not interfere with the binding of ATP to its cognate binding pocket. In a related study, Lu et al proposed that repeated conformational transitions are required for proper substrate binding .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Significantly, a similar hybrid mode of ligand binding has been proposed by previous simulations by Matsunaga et al, and these results are supported by experiments by Ådén et al, who have extensively studied the surface of ligand binding using ATP as a probe molecule . In addition, our results have implications for understanding the allosteric communication between AMP binding and ATP lid closure rates, which is recently proposed by Scheerer et al In particular, they observed increased rates of ATP lid closure in the presence of AMP, while AMP did not interfere with the binding of ATP to its cognate binding pocket. In a related study, Lu et al proposed that repeated conformational transitions are required for proper substrate binding .…”
Section: Discussionsupporting
confidence: 90%
“…They also noted different rates of opening between the apo- and holo-state enzymes, with the opening in the holo-state being faster. More recent sm-FRET studies further confirmed this result with the suggestion of multiple conformational transitions before establishing the correct binding poses of reaction substrates . Similarly, Zheng and Cui, utilizing molecular dynamics (MD) simulations and Markov state modeling (MSM), reported opening rates of an apo-state AK that were orders of magnitude faster than the catalytic turnover rate .…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…30,33,50,56 The apo-enzyme showed one main current level that occasionally switched to a deeper state (M1, IRES M1 = 49.2 ± 0.1 %, kon M1 = 4.66 ± 0.72 s -1 and koff M1 = 55.2 ± 15.8 s -1 , Figure 2A, Figure S3). Previous work indicated that the enzyme might spontaneously close 33,36,41,45,51,53,[67][68][69][70] S2), most likely, representing all possible domain configurations that AK can adopt within the nanopore.…”
Section: Lid and Nmp Domain Motions Induced By Ligandsmentioning
confidence: 99%
“…Structural studies have shown that the LID and NMP domains undergo major conformation changes [31][32][33] , closing over the active site to protect the ligands from hydrolysis. 34 Many studies have attempted to elucidate how dynamics and conformational changes in AK are associated with molecular recognition, catalysis and allostery 33,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] .…”
Section: Introductionmentioning
confidence: 99%